2013
DOI: 10.1021/pr400425f
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Analysis of the Rice Roots Colonized byHerbaspirillum seropedicaeStrain SmR1 Reveals Induction of the Methionine Recycling in the Plant Host

Abstract: Although the use of plant growth-promoting bacteria in agriculture is a reality, the molecular basis of plant-bacterial interaction is still poorly understood. We used a proteomic approach to study the mechanisms of interaction of Herbaspirillum seropedicae SmR1 with rice. Root proteins of rice seedlings inoculated or noninoculated with H. seropedicae were separated by 2-D electrophoresis. Differentially expressed proteins were identified by MALDI-TOF/TOF and MASCOT program. Among the identified proteins of H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…However, down‐regulation of ACC oxidase by 1.5‐fold in both the cultivars indicated that preferential AdoMet pool was not channelized towards ethylene production. A recent proteomic study has shown that increased expression of AdoMet synthetase and lower level of ACC oxidase resulted in higher methionine recycling and lower ethylene biosynthesis in rice roots against Herbaspirillum seropedicae (Alberton et al ., ). Silencing of AdoHcy hydrolase in transgenic tobacco plants confirmed its role in defence mechanism against pathogens (Masuta et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, down‐regulation of ACC oxidase by 1.5‐fold in both the cultivars indicated that preferential AdoMet pool was not channelized towards ethylene production. A recent proteomic study has shown that increased expression of AdoMet synthetase and lower level of ACC oxidase resulted in higher methionine recycling and lower ethylene biosynthesis in rice roots against Herbaspirillum seropedicae (Alberton et al ., ). Silencing of AdoHcy hydrolase in transgenic tobacco plants confirmed its role in defence mechanism against pathogens (Masuta et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…2a). NifH was among the most abundant protein expressed during interaction of H. seropedicae and rice seedlings (Alberton et al 2013).…”
Section: Nitrogen Fixation and Bacterial Adaptation To Microoxic Envimentioning
confidence: 99%
“…seropedicae with different plant hosts (1214). In addition, comparative genomics and metagenomics studies have shown that certain functions, e.g., nutrient transport systems, type IV conjugal DNA-protein transfer secretion systems, plant growth promotion genes, and iron uptake systems, are overrepresented in the genomes of bacterial endophytes, compared to rhizospheric or soil bacteria (4, 1517).…”
Section: Introductionmentioning
confidence: 99%